Marketing of Farm Forestry Produce: a New Challenge for Farmers - Patnaik, A. K. (Indian Forester, 1996)
Marketing seems to be the greatest challenge for the farmers who have adopted Farm Forestry in a big way. The lack of basic knowledge about the marketing, particularly the marketing mechanism like demand supply balance, effective marketing plan, market environment, seems to pose major threat to this great popular movement. In this paper the present scenario of some of the States is analysed and the major constraints in marketing of farm forestry produce are identified and few suggestions to avert these constraints are listed.